Tuberculosis patients with special clinical conditions treated with contezolid: three case reports and a literature review - Wang, Jun; Ma, Liping (Frontiers in Medicine, 2023)
Background Contezolid is a novel oxazolidinone antibacterial agent, but there have been no reports of any pertinent clinical studies for the treatment of tuberculosis (TB). This was the first report of three TB patients who were successfully treated with contezolid. Case presentation Case 1 was TB complicated by myelosuppression syndrome. Case 2 was drug-resistant TB complicated by cirrhosis and anemia. Case 3 was drug-resistant TB complicated by liver transplantation that developed severe anemia after linezolid treatment. Following contezolid therapy, the three patients’ symptoms improved significantly, and no adverse reactions were observed. The chest computed tomography (CT) examination also indicated that the therapeutic effect of this anti-TB regimen was as expected. Conclusion Contezolid showed good efficacy and fewer side effects in the treatment of TB. It may be a promising TB treatment.